The role of emotions in disinformation during the election campaign - Córdoba-Cabús, Alba (2025)
This study analyses the use of emotions in disinformation about the 2024 US elections (n=374). To this end, a content análisis was carried out. The findings confirm a strong emotional presence in electoral disinformation (80.7%), particularly in content related to the campaign (56.7%). This strategy is highly prevalent on social media (76.2%), where the main disseminators are anonymous citizens (42.7%). Emotional patterns tend to be predominantly negative (55.9%) and frequently focus on the candidates (36.8%). The Republican Party emerges as the primary disseminator, making greater use of emotional content to attack (72.8%) and to praise its leader (25.6%). Given the central role of these elections, the disinformation strategies observed may be replicated in other contexts. Understanding how these dynamics operate offers valuable insights for analyzing similar cases in other countries, anticipating future trends, and designing mechanisms to counter this phenomenon, which poses a threat to democratic health.